Fe3O4@Au@mSiO2 as an enhancing nanoplatform for Rose Bengal photodynamic activity. Issue 29 (12th July 2017) - Rosa-Pardo, I.; Roig-Pons, M.; Heredia, A. A.; Usagre, J. V.; Ribera, A.; Galian, R. E.; Pérez-Prieto, J.
Abstract : A novel nanoplatform integrated by core–shell Fe3 O4 @Au nanoparticles encapsulated near the outer surface of mSiO2 nanoparticles has been successfully synthesised and proved to enhance the efficiency of Rose Bengal for singlet oxygen generation. Abstract : A novel nanoplatform composed of three types of materials with different functionalities, specifically core–shell Fe3 O4 @Au nanoparticles encapsulated near the outer surface of mesoporous silica (mSiO2 ) nanoparticles, has been successfully synthesised and used to enhance the efficiency of a photosensitiser, namely Rose Bengal, in singlet oxygen generation. Fe3 O4 is responsible for the unusual location of the Fe3 O4 @Au nanoparticle, while the plasmonic shell acts as an optical antenna. In addition, the mesoporous silica matrix firmly encapsulates Rose Bengal by chemical bonding inside the pores, thus guaranteeing its photostability, and in turn making the nanosystem biocompatible. Moreover, the silica surface of the nanoplatform ensures further functionalisation on demand.